An evaluation of railway passenger transport in Turkey using life cycle assessment and life cycle cost methods. (December 2015) - Banar, Müfide; Özdemir, Alp
Highlights: Railway transportation was evaluated in terms of environmental and economic aspects. A cradle-to-grave LCA was carried out for environmental assessment. A new LCC methodology was developed for economical assessment. LCA and LCC results were integrated. We evaluated LCA methodology to the railway transportation in Turkey. Abstract: In recent years, Turkey's railway transport system has shown considerable improvement. Today, our country has 12, 000 km total rail network; the High Speed Railway (HSR) accounts for 888 km, with the remainder being Conventional Railway (CR). This study aims to assess the railway passenger transportation system in Turkey, an integrated system of HSR/CR, from an environmental and economic point of view, via Life Cycle Assessment (LCA) and Life Cycle Cost (LCC) methodologies. The LCA analysis was realized using SimaPro 7.3.3 software and the CML2 baseline 2000 method for selected impact categories (abiotic depletion, acidification, eutrophication, global warming, human toxicity and fresh water aquatic ecotoxicity). The LCC analysis was performed by developing a cost model for internal (energy, materials, transport) and external (pollutant, accident, noise) cost categories with this software. Our results show that, the total environmental load of HSR is shared by infrastructure and operations, with percentages of 58% and 42%, respectively. On the other hand, for CR, infrastructure created 39% of the total environmental load, while operations had 61%. Regarding cost, the impact in HSR resulted from infrastructure and operations, with percentages of 69% and 31%, respectively. In the CR system, infrastructure caused 21% of the total cost impact while operations led to 69%. The results are interpreted in the light of a Monte Carlo simulation analysis, performed to gauge the effects of data variation on the results. By providing insight through this study, evaluation of all railway transportation systems should be possible using only LCA/LCC methodologies.